Pond Niche Based Integrated Farming: A Case Study in Tripura, India - Singh, Nongthombam Dorendo; Sarkar, Atanu; Biswas, Pradyut; Pal, Prasanjit; Upadhyay, Anil Datt (International Journal of Bio-resource and Stress Management, 2018)
The article is based on a study conducted during December, 2016 to February, 2017 in West Tripura district of Tripura (India) to examine the status of pond niche based integrated farming and identify perceived constraints associated with systematic practicing of the same. Findings suggested that despite pursuing of integrated farming in varied forms with practice of fish culture alongside different combinations of other enterprises, the average fish productivity for in-practice respondents was only 515.89 kg ha-1, which was lagging behind by 4.70 times than the state average (2429.20 kg ha-1) and around 5.13 times than the average of district under study (2650.40 kg ha-1). Further, the average annual income flow by combining all pond niche based enterprises was also insufficient (Rs. 19641/- per surveyed household). This suggested only limited success of the fish based integrated farming in the study area. The most important constraints perceived as deterring systematic practicing of integrated farming were: ‘no clear idea on how to effectively integrate crop, livestock etc. around the pond’; ‘dearth of required technical guidance from a single institutional source in a synchronized manner’; ‘lack of extension activity to locally demonstrate worthiness of integrated farming and/or exposure visit to successful sites to show how things have happened’; ‘business/service/agriculture/wage earning being main occupation, can’t concentrate seriously on integration’; and ‘inadequate training support on the subject’. Therefore, much more systematic institutional interventions are required for due ideation, motive building and skill empowerment on the domain of aquatic niche based integrated farming.